Depression, excessive alcohol consumption and nalmefene. Issue 5 (September 2014) - Allen, Danny
<x xml:space="preserve">Abstract</x> It is common for people with low mood to drink alcohol to excess, thus setting up a cycle of worsening depression. It is well recognised that antidepressants are not a stand‐alone treatment and that concurrent treatment to help the patient reduce or stop drinking is also required. This article describes how nalmefene, a relatively new drug which helps reduce alcohol comsumption, was used effectively in a woman with depression.